Brønsted Acid Catalyzed Dehydrative Arylation of 4-Indolylmethanols with Indoles: Efficient Access to Indolyl-Substituted Triarylmethanes - Liu, Jin-Xi; Zhu, Zi-Qi; Yu, Lei; Du, Bai-Xiang; Mei, Guang-Jian; Shi, Feng (Synthesis, 2018)
A Brønsted acid catalyzed dehydrative arylation of 4-indolylmethanols with indoles has been established, leading to a series of indolyl-substituted triarylmethanes in good to excellent yields (up to 97% yield). In addition, in this Brønsted acid catalyzed dehydration process, the only byproduct was water. Accordingly, this approach can be considered to have high atom economy and to be environmentally friendly. This approach not only provides a useful strategy for the synthesis of structurally diversified indolyl-substituted triarylmethanes, but also represents the first example of a 4-indolylmethanol-involved reaction, which will advance the chemistry of indolylmethanols.
Keywords: indolylmethanol; triarylmethane; Brønsted acid catalysis; indole